Agent-based framework for improving coordination of urban infrastructure provision for new residential areas in Iran - Yazdani, Saeid (2015)
Urban infrastructures are the main structure of cities, providing potable water, sanitary sewage, mobility, communication, power, and energy. Provision of urban infrastructure systems is a priority in any kind of urban development since without these critical urban systems proper urban development would not be possible. The involvement of different governmental agencies in the process of the urban infrastructure provision requires coordination between these independent agencies, which is an important aspect of the process.This research was prompted by the problem of a lack of coordination between urban infrastructure agencies (UIAs), which gives rise to numerous coordination challenges in the context of urban infrastructure provision in Iran. The aim of this research is to develop and validate an agent-based framework to coordinate the activities of the different agencies involved in the process of urban infrastructure provision in Iran. In order to achieve this, three objectives were developed:To identify and document the barriers impede coordination and drawbacks of lack of coordination in the context of urban infrastructure provision for new residential areas; to analyze and document the various kinds of interdependency among agencies involved in the process of urban infrastructure or new residential areas; and to develop and validate an agent-based framework for coordinating interdependencies among agencies involved in the process of urban infrastructure provision. Toward this end, a Sequential Mixed-method Multiple Case Study, comprising the process of infrastructure provision for five new residential sites in Iran, was designed and conducted. Research findings can be summarized as follows. Firstly, drawbacks of lack of coordination in the context of infrastructure provision can be categorized into seven major problems, such as increased project time and cost, duplication of activities, and the like. Secondly, seven types of coordination barriers can be addressed in the context of infrastructure provision, including differences in governance and management structures, frequent changes in organizational positions,and political pressure, among others. Thirdly, during the three main stages of infrastructure provision for new residential areas there are various kinds of interdependencies such as timing interdependency, resource interdependency, and requisite interdependency. Finally, this research by hybridization of the coordination science and agent-based paradigm, develops and validates an agent-based coordination framework (ABC-framework) to manage the identified interdependencies.To sum up, by identifying different kinds of interdependencies in the context of urban infrastructure provision, it may provide an empirical guide for decision-makers to consider the potentials and limitations of urban infrastructure systems during the planning of new residential areas. Moreover, it may also offer a logical way for managing the complex process in the domain of urban development issues by means of a set of simple "if-then" roles.